Sex Mediates the Effects of High-Definition Transcranial Direct Current Stimulation on "Mind-Reading". (16th December 2017) - Martin, A.K.; Huang, J.; Hunold, A.; Meinzer, M.
Highlights: Sex mediates HD-tDCS response on the Reading the Mind in the Eyes test. Sex mediated differences in the dorsomedial prefrontal cortex for ToM. Future ToM studies using tDCS need to consider sex. Abstract: Sex differences in social cognitive ability are well established, including measures of Theory of Mind (ToM). The aim of this study was to investigate if sex mediates the effects of high-definition transcranial direct current stimulation (HD-tDCS) administered to a key hub of the social brain (i.e., the dorsomedial prefrontal cortex, dmPFC) on the Reading the Mind in the Eyes Test (RMET). Forty healthy young adults (18–35 years) were randomly allocated to receive either anodal or cathodal HD-tDCS in sham HD-tDCS controlled, double blind designs. In each of the two sessions, subjects completed the RMET. Anodal stimulation to the dmPFC increased accuracy on the RMET in females only. To assure regional specificity we performed a follow-up study stimulating the right temporoparietal junction and found no effect in either sex. The current study is the first to show improved performance on the RMET after tDCS to the dmPFC in females only. The polarity-specific effects and use of focal HD-tDCS provide evidence for sex-dependent differences in dmPFC function in relation to the RMET. Future studies using tDCS to study or improve ToM, need to consider sex.